Interventions to improve team effectiveness within health care: a systematic review of the past decade - Martina Buljac-Samardzic; Kirti D. Doekhie; Jeroen D. H. van Wijngaarden (BMC, 2020)
Abstract Background A high variety of team interventions aims to improve team performance outcomes. In 2008, we conducted a systematic review to provide an overview of the scientific studies focused on these interventions. However, over the past decade, the literature on team interventions has rapidly evolved. An updated overview is therefore required, and it will focus on all possible team interventions without restrictions to a type of intervention, setting, or research design. Objectives To review the literature from the past decade on interventions with the goal of improving team effectiveness within healthcare organizations and identify the "evidence base" levels of the research. Methods Seven major databases were systematically searched for relevant articles published between 2008 and July 2018. Of the original search yield of 6025 studies, 297 studies met the inclusion criteria according to three independent authors and were subsequently included for analysis. The Grading of Recommendations, Assessment, Development, and Evaluation Scale was used to assess the level of empirical evidence. Results Three types of interventions were distinguished: (1) Training, which is sub-divided into training that is based on predefined principles (i.e. CRM: crew resource management and TeamSTEPPS: Team Strategies and Tools to Enhance Performance and Patient Safety), on a specific method (i.e. simulation), or on general team training. (2) Tools covers tools that structure (i.e. SBAR: Situation, Background, Assessment, and Recommendation, (de)briefing checklists, and rounds), facilitate (through communication technology), or trigger (through monitoring and feedback) teamwork. (3) Organizational (re)design is about (re)designing structures to stimulate team processes and team functioning. (4) A programme is a combination of the previous types. The majority of studies evaluated a training focused on the (acute) hospital care setting. Most of the evaluated interventions focused on improving non-technical skills and provided evidence of improvements. Conclusion Over the last decade, the number of studies on team interventions has increased exponentially. At the same time, research tends to focus on certain interventions, settings, and/or outcomes. Principle-based training (i.e. CRM and TeamSTEPPS) and simulation-based training seem to provide the greatest opportunities for reaching the improvement goals in team functioning.